The Student’s Perceptions towards the Use of Google Classroom in Online Classes - Rahmani, Eka Fajar; Eka Putri Wahyuni; Irma Rahmawati; Indah, Indah (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this research is to identify and describe the perception of the sixth-semester students towards the use of Google Classroom in online classes. The subjects of this study were fifty-six Regular A students, in the English Language Education study program, Universitas Tanjungpura. The data in this descriptive study were collected through a close-ended questionnaire which was divided into two sections, students' perception and features of Google Classroom. Furthermore, the data in this study were analyzed using descriptive statistics which were described and interpreted through diagrams and pie charts. The research findings indicate that most students have positive perceptions towards the use of Google Classroom in online classes. In addition, the feature that helps students the most in online classes is submitting assignments. In short, it can be concluded that Google Classroom has played an essential role during online classes in terms of its accessibility and feature of assignment submission section.